dado o polinomio p(x) = 3x-x²+3, calcule p(0) + p(-1) - 3 p(1/2)
Soluções para a tarefa
Respondido por
0
p(0) = 3
p(-1) = -1
p(1/2) = 7/2
Na formula: p(0) + p(-1) -3 P(1/2)
Entao, substituindo: 3 + (-1) - 3 . (7/2)
o resultado será>>>> -3/2
p(-1) = -1
p(1/2) = 7/2
Na formula: p(0) + p(-1) -3 P(1/2)
Entao, substituindo: 3 + (-1) - 3 . (7/2)
o resultado será>>>> -3/2
Perguntas interessantes
Geografia,
11 meses atrás
Matemática,
11 meses atrás
Matemática,
1 ano atrás
Física,
1 ano atrás
Português,
1 ano atrás
Ed. Moral,
1 ano atrás